PEMERIKSAAN GOLONGAN DARAH DI PONDOK TAHFIDZ AL QUR’AN AS SYUHADA FII SABILILLAH KECAMATAN TAMALANREA KOTA MAKASSAR - Sulfiani Sulfiani; Nuramaniyah Taufiq; Hartati Hartati; Olin Toyi (STAI Darul Qalam Tangerang, 2022)
One of the prevention efforts in handling complications of the disease is to do a blood type examination. Blood type is an important thing in donating, because someone who gets a blood transfusion must match the blood group of the donor. Blood transfusion of incompatible groups can cause several immunological transfusion reactions and clinical aspects such as incompatibility of the ABO blood group system. Knowing blood type is an important part for every human being. Many of us don't know what type of blood type we have.. This case becomes very crucial when the individual experiences an accident, such as an accident that involves a lot of blood coming out. The action of handling the patient becomes late, because this individual does not yet know the type of blood group he has. Knowing your blood type helps the body stay healthy, plan for the future and prevent complications. Based on the survey and interviews of the service team with the caretaker of the cottage, there are still some residents in the cottage who do not know their blood type. so that the service team carries out community service activities in the form of blood type checks. The purpose of this community service is to find out the blood type of the residents of the Tahfidz Al Qur'an As-Syuhada Fii Sabilillah cottage, Tamalanrea District, Makassar City. There are three stages carried out in this activity, namely the planning stage, the preparation stage and the implementation stage. At the implementation stage, the blood group examination is carried out using the slide method which is a simple, fast and easy method. This blood type examination was attended by 46 residents of the cottage, male and female and aged 1-50 years. The results obtained from the blood group examination are that there are residents of the cottage who have blood type A as much as 23.90%, who have blood type B as much as 39.10% and who have blood type AB as much as 2.20% and who have blood type O as much as 34 ,80 %